Use of Additive Technologies in Lower Limb Prosthetics - E. B, Ivanova; A.V, Torchinskaya (International Journal of Engineering and Technology, 2018)
This article is devoted to the development of methods for manufacture of the receiving sleeve of the lower limb prosthesis (PNC) using additive technologies. The technique allows the most accurate transfer of geometry of the patient's stump, increases the speed of its manufacture and provides a non-contact type of interaction with the patient. The proposed development is of interest, as for orthopedic surgeons, and for specialists of companies producing PNK. The use of additive technologies helps to optimize and accelerate the technological process of manufacturing NCP at certain stages, which in turn leads to a decrease in the cost of final products and the time of their production.Â Â